Sosialisasi Dan Pelatihan Proses Pembuatan Serat Abaca Dari Pohon Pisang Abaca Di Kabupaten Kepulauan Talaud Propinsi Sulawesi Utara - Abdul Haris; Hermanto; Misdiyanto; Yoyok (Universitas Lancang Kuning, 2020)
Abaca banana trees thrive in the Talaud Islands, North Sulawesi Province, which is the outermost archipelago and is close to the Philippines. In this community service, socialization and training have been held on the processing of Abaca banana trees using a shaved machine (decorticator) into Abaca fiber. The decorticator machine made itself to be taken to the Talaud Islands for training for the people of South Essang District. Socialization to the leaders of Indigenous Peoples and Government expressed their supportive attitude by holding this socialization. And next is the fiber making training that is attended by some people of South Essang District, people can do fiber making and the results after the drying process are in accordance with the quality with a moisture content of less than 30%. Furthermore, will to the use of Abaca fiber will be studied further.